Analisis Faktor-faktor Yang Mempengaruhi Kepuasan Tamu Favehotel Gatot Subroto Jakarta - I Nyoman Iswara Prabawa (Journal of Applied Management Research, 2022)
This study aims to determine the strategic factors and their relationship in improving the level of guest satisfaction at favehotel Gatot Subroto Jakarta. This study aims to determine the strategic factors and their relationship in increasing guest satisfaction at Favehotel Gatot Subroto Jakarta. This study uses a structural analysis approach. The analytical method uses MICMAC to identify the most influential variables and their relationship to guest satisfaction at Favehotel Gatot Subroto Jakarta. The results of the analysis that embody the typology of strategic variables based on the strength of influence found 19 strategic variables classified in 4 quadrants, namely: (1) Dominant variables consist of: 3 variables, 2 price dimensions and 1 location dimension, (2) Key variables consist of: 7 variables (2 dimensions of product, 2 dimensions of facilities, 2 dimensions of atmosphere, and 1 dimension of promotion). (3) The output variable consists of: 1 variable (1 service dimension). (4) Autonomous variables consist of: 8 variables (3 service dimensions, 2 promotion dimensions, 1 location dimension, 1 facility dimension, 1 location dimension). The results of this study indicate various sources of information for policy makers in increasing guest satisfaction at Favehotel Gatot Subroto Jakarta.